Carboxymethyl chitosan prolongs adenovirus‐mediated expression of IL‐10 and ameliorates hepatic fibrosis in a mouse model. Issue 3 (10th March 2022) - Gou, Yannian; Weng, Yaguang; Chen, Qian; Wu, Jinghong; Wang, Hao; Zhong, Jiamin; Bi, Yang; Cao, Daigui; Zhao, Piao; Dong, Xiangyu; Guo, Meichun; Wagstaff, William; et al.
Abstract: Effective and safe liver‐directed gene therapy has great promise in treating a broad range of liver diseases. While adenoviral (Ad) vectors have been widely used for efficacious in vivo gene delivery, their translational utilities are severely limited due to the short duration of transgene expression and solicitation of host immune response. Used as a promising polymeric vehicle for drug release and nucleic acid delivery, carboxymethyl chitosan (CMC) is biocompatible, biodegradable, anti‐microbial, inexpensive, and easy accessible. Here, by exploiting its biocompatibility, controlled release capability and anti‐inflammatory activity, we investigated whether CMC can overcome the shortcomings of Ad‐mediated gene delivery, hence improving the prospect of Ad applications in gene therapy. We demonstrated that in the presence of optimal concentrations of CMC, Ad‐mediated transgene expression lasted up to 50 days after subcutaneous injection, and at least 7 days after intrahepatic injection. Histologic evaluation and immunohistochemical analysis revealed that CMC effectively alleviated Ad‐induced host immune response. In our proof‐of‐principle experiment using the CCl4 ‐induced experimental mouse model of chronic liver damage, we demonstrated that repeated intrahepatic administrations of Ad‐IL10 mixed with CMC effectively mitigated the development of hepatic fibrosis. Collectively, these results indicate that CMC can improve the prospect of Ad‐mediated gene therapy by diminishing the host immune response while allowing readministration and sustained transgene expression.